Autogenous Transcriptional Regulation of the regA Gene, Encoding an AraC-Like, Essential Virulence Regulator in Citrobacter rodentium - Tan, Aimee (American Society for Microbiology (ASM), 2011)
We identified several promoters responsible for the expression of regA, which encodes a global virulence regulator in Citrobacter rodentium. Expression of some of the promoters was strongly autoactivated by RegA in conjunction with bicarbonate. Biochemical and mutational analyses were used to determine the consensus sequence of the RegA-binding sites.